Phenol Coefficient Test Combination Infusion of Cananga odorata – Averrhoa bilimbi L. Against Staphylococcus aureus and Salmonella typhi in Vitro - Budiarti, Lia Yulia; Wydiamala, Erida; Ulfa, Najiya (Future Science, 2021)
Cananga odorata (kenanga) flowers and Averrhoa bilimbi L. (belimbing wuluh) fruit are plant parts that contain relatively the same antibacterial compounds, namely flavonoids, saponins, and tannins. Both of these plants can be developed as an alternative natural antiseptic preparation, which is made in the form of a combination infusion. The effectiveness of an antiseptic preparation is measured by the coefficient value of the phenol antiseptic substance compared to 5% phenol against several standard test bacteria. This study aims to determine the antibacterial activity of the combination infusion of Cananga odorata flower - Averrhoa bilimbi L. fruit against Staphylococcus aureus ATCC 25923 and Salmonella typhi ATCC 19430 based on the in vitro phenol coefficient test. The phenol coefficient test method was carried out conventionally. The coefficient value close to 1 can be said that the antiseptic preparation has good activity and is equivalent to the phenol coefficient value as a comparison. The results showed that the mean coefficient of the phenol coefficient of the combination infusion of Cananga odorata flower - Averrhoa bilimbi L. fruit was 0.91 against S. aureus and 0.83 against S. typhi. The conclusion of this study, the antibacterial activity of the combination infusion of Cananga odorata flower - Averrhoa bilimbi L. fruit against Staphylococcus aureus obtained a higher phenol coefficient value than Salmonella typhi.